Labor induction and cesarean delivery: A prospective cohort study of first births in Pennsylvania, USA. Issue 3 (21st March 2017) - Kjerulff, Kristen H.; Attanasio, Laura B.; Edmonds, Joyce K.; Kozhimannil, Katy B.; Repke, John T.
Abstract: Background: Mode of delivery at first childbirth largely determines mode of delivery at subsequent births, so it is particularly important to understand risk factors for cesarean delivery at first childbirth. In this study, we investigated risk factors for cesarean delivery among nulliparous women, with focus on the association between labor induction and cesarean delivery. Methods: A prospective cohort study of 2851 nulliparous women with singleton pregnancies who attempted vaginal delivery at hospitals in Pennsylvania, 2009‐2011, was conducted. We used nested logistic regression models and multiple mediational analyses to investigate the role of three groups of variables in explaining the association between labor induction and unplanned cesarean delivery—the confounders of maternal characteristics and indications for induction, and the mediating (intrapartum) factors—including cervical dilatation, labor augmentation, epidural analgesia, dysfunctional labor, dystocia, fetal intolerance of labor, and maternal request of cesarean during labor. Results: More than a third of the women were induced (34.3%) and 24.8% underwent cesarean delivery. Induced women were more likely to deliver by cesarean (35.9%) than women in spontaneous labor (18.9%), unadjusted OR 2.35 (95% CI 1.97‐2.79). The intrapartum factors significantly mediated the association between labor induction and cesarean delivery (explaining 76.7% of this association), particularly cervical dilatation <3 cm at hospital admission, fetal intolerance of labor, and dystocia. The indications for labor induction only explained 6.2%. Conclusions: Increased risk of cesarean delivery after labor induction among nulliparous women is attributable mainly to lower cervical dilatation at hospital admission and higher rates of labor complications.